2016
DOI: 10.1016/j.lwt.2016.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Developing gluten free bakery improvers by hydrothermal treatment of rice and corn flours

Abstract: 13The impact of hydrothermal treatment of rice and corn flours on their potential as gluten free 14 bakery improvers was tested. Hydrothermal treatment of flours was carried out by 15 suspending flours in water on the basis of 5/1 (w/w) and heated until 65°C. Corn or rice 16 semolina supplemented by faba bean semolina in ratio of 2/1 (w/w) were used for obtaining 17 protein enriched gluten free breads, where improvers functionality was tested. Two central 18 composite designs involving water hydration levels (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 23 publications
2
47
0
3
Order By: Relevance
“…For all crumb properties (hardness, chewiness, and springiness), water showed a significant effect as reported by numerous authors [5,31].…”
Section: Influence Of Factors On Bread Crumb Texturesupporting
confidence: 74%
See 3 more Smart Citations
“…For all crumb properties (hardness, chewiness, and springiness), water showed a significant effect as reported by numerous authors [5,31].…”
Section: Influence Of Factors On Bread Crumb Texturesupporting
confidence: 74%
“…The gluten-free bread making process was performed according to Bourekoua et al [5]. A control gluten-free bread made without any additives with 75 g water/100 g of formula, fixed according to our preliminary trials, was used.…”
Section: Baking Testsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients showing nutritional deficiencies could require supplementation of their diets with vitamins, antioxidants, minerals, and proteins to correct deficiencies and restore nutrient reserves [17,18]. Bourekoua et al [19] reported that celiac disease suffers from the lack of glutenfree products with the subsequent negative effects on nutritional and health status of patients.…”
Section: Introductionmentioning
confidence: 99%